2011
DOI: 10.2215/cjn.00710111
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Prediction of 1-Year Mortality in Prevalent Hemodialysis Patients

Abstract: SummaryBackground and objectives Measurement of C-reactive protein (CRP) levels remains uncommon in North America, although it is now routine in many countries. Using Dialysis Outcomes and Practice Patterns Study data, our primary aim was to evaluate the value of CRP for predicting mortality when measured along with other common inflammatory biomarkers.Design, setting, participants, & measurements We studied 5061 prevalent hemodialysis patients from 2005 to 2008 in 140 facilities routinely measuring CRP in 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
119
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 49 publications
15
119
2
5
Order By: Relevance
“…14 Furthermore, a large international study of HD patients demonstrated that CRP improved the 1-year mortality prediction. 15 The 3 biomarkers (TnT, BNP, and CRP) individually assess different pathophysiological pathways (ie, myocardial injury, left ventricular wall stress, and inflammation, respectively); moreover, they are readily measured, easily accessible, relatively inexpensive, and reproducible. 16 We prospectively investigated whether the combined use of these biomarkers could improve the prediction of long-term mortality in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, a large international study of HD patients demonstrated that CRP improved the 1-year mortality prediction. 15 The 3 biomarkers (TnT, BNP, and CRP) individually assess different pathophysiological pathways (ie, myocardial injury, left ventricular wall stress, and inflammation, respectively); moreover, they are readily measured, easily accessible, relatively inexpensive, and reproducible. 16 We prospectively investigated whether the combined use of these biomarkers could improve the prediction of long-term mortality in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Postdialysis electrolyte levels are measured often in many countries; serum fibrinogen, Btype natriuretic peptide, and troponin levels are common in a few countries. Our large longitudinal database of CRP levels formed the basis for a recent publication describing the range of CRP levels in routine dialysis practice, as well as the added prognostic information gained by CRP even when measured along with inflammatory markers relied on in the United States such as serum albumin and ferritin levels (5). Future analysis will evaluate whether physician responses to elevated CRP levels help to improve clinical outcomes.…”
Section: Dopps Goals Design and Datamentioning
confidence: 99%
“…Yaklaşık 5000 hemodiyaliz hastası ile yapılmış bir çalışmada CRP düzeyi ile mortalite pozitif olarak ilişkili bulunmuştur. Bu nedenle CRP'nin özellikle hemodiyaliz tedavisi alan hastalarda takip edilmesi gereken standart bir biyokimyasal parametre olması gerektiği öne sürülmüştür (34). Son evre böbrek yetmezliği olan hastalarda IL-6'nın mortalite ve KVH'nın tahmin edilmesinde en önemli inflamatuvar belirteç olduğu gösterilmiştir (35).…”
Section: Kronik Böbrek Hastaliğiunclassified